Evaluating association between implementation of ISO 14031 guidelines and ISO 14001 certification by industrial sector in Saudi Arabia - Mansour, Mohamed; Alsulamy, Saleh (Journal of Environmental Engineering and Landscape Management, 2021)
Conflicting research results regarding the application of environmental management systems on the environmental performance of industrial organizations between positive, negative, and no effect made studying this relationship a complex research problem. This study aimed to assess the extent of the commitment of industrial organizations in Saudi Arabia in applying ISO 14031:2013 guidelines to evaluate environmental performance and to study the association between the guideline implementation by ISO 14001:2015 certified and uncertified organizations. Using the descriptive approach, the association was identified between 13 independent variables representing ISO 14031:2013 guidelines for environmental performance evaluation and ISO 14001:2015 certification based on a 596 organizations survey conducted from May to December 2020, in addition to comparing the results of the study with similar studies. The results showed a medium positive correlation of ISO 14031 measurement variables with ISO 14001 certification. The study answered the question concerning the association of implementing of ISO 14031 guidelines to evaluate the environmental performance of ISO 14001 certified or uncertified organizations. Limited resources organizations should focus on monitoring environmental indicators and concentrate of planning activities to ensure the organizations uses environmental condition indicators data efficiently. Future studies are necessary to determine causal relationships, to develop specific environmental performance measures, and to integrate ISO 14031 in ISO 14001.